Neanderthal exploitation of birds in north-western Europe: Avian remains from Scladina Cave (Belgium) - Goffette, Quentin; Rots, Veerle; Abrams, Grégory; Pirson, Stéphane; Di Modica, Kévin; Bray, Fabrice; Cnuts, Dries; Bonjean, Dominique; Amos, Linda (Frontiers in Environmental Archaeology, 2024)
For a long time, Neanderthals were considered hunters of large mammals, whereas the diversification of the exploited faunal spectrum to include smaller taxa, including birds, was assumed to be specific to anatomically modern humans. In recent decades, archeozoological analyses of faunal remains from layers associated with Middle Paleolithic lithic industries have revealed traces of human manipulation of small taxa, indicating the exploitation of a wider range of animals than previously thought. These new data have challenged the view that Neanderthals did not exploit small animals, thereby narrowing the behavioral gap with anatomically modern humans. Nevertheless, the information currently available comes almost exclusively from southern Europe and the nature of Neanderthal small fauna exploitation in northern Europe remains largely unknown. The present study aims to fill this gap by applying archeozoological methods, including detailed taphonomic and traceological analyses, to 119 bird remains recovered from layers containing Middle Paleolithic industries at Scladina Cave, Belgium. Analyses of proteomics were applied to clarify the taxonomic identity of two morphologically non-diagnostic elements. Modifications made by non-human predators or scavengers, suggest that mammalian carnivores are responsible for accumulating a considerable portion of the avian assemblage. In total, seven bird bones exhibit anthropogenic marks, and one element presents questionable marks. Various Galliformes taxa and a great cormorant were exploited likely for their meat. The talon of a likely lesser spotted eagle displays intense polishing possibly linked to human manipulation of this element, although this remains hypothetical. On the radius of a Western capercaillie, two deep incisions may indicate bone working, and intense use-wear indicates that the bone has been utilized, potentially on soft organic material. This study provides the first evidence of the exploitation of birds by Neanderthal in Belgium and constitutes the only detailed zooarchaeological analysis of Middle Paleolithic bird material in northwestern Europe. The likely modification and subsequent utilization of a bird bone is only the second example known from Neanderthal occupations in Eurasia. The novel taxa identified as Neanderthal prey highlight the plasticity of Neanderthal ecological behavior, adapting to different landscapes and climates and exploiting a large spectrum of locally available prey.